Determinan Faktor Internal Dana Pihak Ketiga dan Faktor Eksternal (Inflasi, Pendapatan Perkapita, dan Imbalan SWBI) Terhadap Jumlah Dana Talangan Haji Pada Bank Syariah (BNI Syariah, BRI Syariah, Bank Muamalat, Bank Syariah Mandiri) Periode 2009-2014 - Fachmi Setyawan; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aimed to analyze the influence of internal factors of Islamic banks are third party funds and macroeconomic factors, namely inflation, percapita income and rewards Wadiah Certificate of Bank Indonesia to the amount of their bailout Hajj by Sharia banks in Indonesia during the period January 2009 to December 2014. The approach using multiple linear regression analysis. In this study, most of the hypothesis is not proven. Only variables percapita income and rewards SWBI that meet the research hypothesis. Research shows that third party funds and variable inflation rate indication hit double colinearity problems, so as to avoid bias regression results of these two variables were excluded from the regression model. Percapita income and rewards SWBIs have a significant effect partially to the amount of their bailout Hajj. Effect relationship shown is the reward SWBI have a negative effect, while percapita income has a positive influence on the amount of their bailout Hajj.